Plants and Light Manipulation: The Integrated Mineral System in Okra Leaves. Issue 5 (26th February 2017) - Pierantoni, Maria; Tenne, Ron; Brumfeld, Vlad; Kiss, Vladimir; Oron, Dan; Addadi, Lia; Weiner, Steve
Abstract : Calcium oxalate and silica minerals are common components of a variety of plant leaves. These minerals are found at different locations within the leaf, and there is little conclusive evidence about the functions they perform. Here tools are used from the fields of biology, optics, and imaging to investigate the distributions of calcium oxalate, silica minerals, and chloroplasts in okra leaves, in relation to their functions. A correlative approach is developed to simultaneously visualize calcium oxalates, silica minerals, chloroplasts, and leaf soft tissue in 3D without affecting the minerals or the organic components. This method shows that in okra leaves silica and calcium oxalates, together with chloroplasts, form a complex system with a highly regulated relative distribution. This distribution points to a significant role of oxalate and silica minerals to synergistically optimize the light regime in the leaf. The authors also show directly that the light scattered by the calcium oxalate crystals is utilized for photosynthesis, and that the ultraviolet component of light passing through silica bodies, is absorbed. This study thus demonstrates that calcium oxalates increase the illumination level into the underlying tissue by scattering the incoming light, and silica reduces the amount of UV radiation entering the tissue. Abstract : Calcium oxalate and silica minerals are common components of plant leaves . Little is known about their functions. A correlative approach to visualize calcium oxalates, silica, chloroplasts, and soft tissue in 3D was developed. The authors show how calcium oxalates increase the illumination into the underlying tissue by scattering light, and silica reduces the amount of UV radiation entering the tissue.